From technology adoption to scientific application: impact mechanism analysis of private agricultural extension services promoting scientific fertilization of farmers - Wang, Pan; Li, Hui; Huang, Yanzhong; Qu, Zongru; Liu, Di (Frontiers in Sustainable Food Systems, 2025)
IntroductionPrivate agricultural extension services play an increasingly vital role in agricultural technology dissemination.MethodsUsing multiple econometric models and survey data from 1,246 farmers in Hubei Province, this study examines the effects and underlying mechanisms of private agricultural extension services on farmers’ decisions to adopt scientific fertilization technologies.ResultsThe findings reveal three key insights: First, these services positively influence farmers’ fertilization behavior, significantly increasing their adoption of scientific fertilization technologies and promoting their proper application. Second, Private agricultural extension services can promote farmers to adopt scientific fertilization technology through value perception and technology trusteeship. Third, heterogeneity analysis identifies technology-specific differences in the impact of private agricultural extension services on adoption decisions, showing stronger effects on the adoption of efficient fertilization techniques compared to novel fertilizer products.DiscussionThe research illuminates the micro-mechanisms through which private agricultural extension services operate and supports building a dual-driven “government-led, market-driven” agricultural technology diffusion system.